The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s0102-86502015001000008
|View full text |Cite
|
Sign up to set email alerts
|

Ozone oxidative preconditioning protects the rat kidney from reperfusion injury via modulation of the TLR4-NF-κB pathway

Abstract: PURPOSE:To investigate the protective effects of ozone oxidative preconditioning (OzoneOP) were associated with the modulation of TLR4-NF-κB pathway. METHODS:Thirty six rats were subjected to 45 min of renal ischemia, with or without treatment with OzoneOP (1 mg/kg). Blood samples were collected for the detection of blood urea nitrogen and creatinine levels. Histologic examinations were evaluated and immunohistochemistry was also performed for localization of TLR4 and NF-κB. The expression of TNF-α, IL-1β, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
2
31
0
1
Order By: Relevance
“…39 Ameliorative effect of OT on oxidative stress in our study is also in agreement with those displayed in researches related with ischemia/reperfusion injury in kidney. 37,38,40,41 In conclusion,…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…39 Ameliorative effect of OT on oxidative stress in our study is also in agreement with those displayed in researches related with ischemia/reperfusion injury in kidney. 37,38,40,41 In conclusion,…”
Section: Discussionmentioning
confidence: 74%
“…It has also been shown that ozone administration stimulates oxidative preconditioning or enhances adaptation to oxidative stress involving glutathione, SOD, and catalase and enzymatic reactions, preparing the host to face physiopathological conditions mediated by ROS/ RNS. 37,38 In light of recent pharmacological knowledge, our consideration is that ozone acts as a pro-drug and induces a rearrangement of the biochemical pathways with the activation of a second messenger in a cascade with a multiple system action. 39 Ameliorative effect of OT on oxidative stress in our study is also in agreement with those displayed in researches related with ischemia/reperfusion injury in kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ozone therapy was reported to limit the effects of experimentally induced I/R injury in multiple organs (24,25). Xing et al (26) reported that tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-6, in- MWM; Morris water maze, PFT; platform fi nding time, data given are mean ± SD, P 0 : Indicates the difference in PFT from day 1 to day 4 within each group, P 1 , P 2 , P 3 , P 4 , P 5 , and P 6 indicates the difference in PFT between the sham and control groups, between the sham and ozone1 groups, between the sham and ozone2 groups, between the control and ozone1 groups, between the control and ozone2 groups, and between the ozone1 and ozone2 groups, respectively…”
Section: Discussionmentioning
confidence: 99%
“…Based on these fi ndings, Xing et al (26) suggested that ozone OP exerted a potent anti-infl ammatory effect via modulation of TLR4 and NF-kappa. Wang et al (6) reported a signifi cant decrease in renal fi brosis in response to ozone OP in rats with experimentally induced renal I/R.…”
Section: Tab 2 Mean Mwm Pft On Days 1-4mentioning
confidence: 99%
“…[12][13][14] Lately the anti-inflammation action of this magical treatment has been recognized by some researchers in animal experiments and the mechanisms involved in may associate with the mediation of TLR4. [15][16][17][18] However, whether ozone therapy could also be a promising strategy ameliorating chronic tubuleinterstitial inflammation in CKD patients or CKD animal models has not been discussed yet. Therefore, this paper created a rat model of CKD and aimed at investigating whether ozone therapy could ameliorate tubulointerstitial inflammation by the regulation of TLR4.…”
Section: Introductionmentioning
confidence: 99%